2019
DOI: 10.3389/fgene.2019.00363
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of WRKY Genes and Their Response to Hormone and Mechanic Stresses in Carrot

Abstract: The WRKY gene family plays a vital role in plant development and environment response. Although previous studies suggested that the WRKY genes in carrot (Kuroda type) involved in biotic and abiotic stress responses, the information of WRKY genes in the latest version of the carrot genome ( Daucus carota v2.0, Nantes type carrot) and their response to hormone and injury stresses have not been reported. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 85 publications
(114 reference statements)
4
21
0
Order By: Relevance
“…Some motifs were located nearby the WRKY domain, for instance, motifs 6, 9, and 17. Just as phylogenetic analysis divided Sb WRKY genes into groups I-III and subgroups IIa-e, the presence or absence of shared motifs between Sb WRKY proteins followed the same general separation into groups, consistent with previous studies [ 76 79 ]. Indeed, each of these motifs occurs in most subgroups, and each subgroup can be distinguished based on the motifs they present.…”
Section: Discussionsupporting
confidence: 89%
“…Some motifs were located nearby the WRKY domain, for instance, motifs 6, 9, and 17. Just as phylogenetic analysis divided Sb WRKY genes into groups I-III and subgroups IIa-e, the presence or absence of shared motifs between Sb WRKY proteins followed the same general separation into groups, consistent with previous studies [ 76 79 ]. Indeed, each of these motifs occurs in most subgroups, and each subgroup can be distinguished based on the motifs they present.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, 490 WRKY gene family members were identified from six species of the superorder Asteranae. We identified 65 WRKY genes in carrot, which compares with 67 in a previous study of the same variety [29]. This difference may be due to the fact that the E values were set differently when the domains were screened.…”
Section: Discussionmentioning
confidence: 96%
“…sativus L.; Daucus carota L. cv. Kuroda) [25,26,27,28,29,30]. Within superorder the Asteranae, genomes of six species of the Asterales and the Apiales have been sequenced.…”
Section: Introductionmentioning
confidence: 99%
“…Evolutionary alterations have helped plants adapt to abiotic and biotic stresses by controlling a network of certain genes through modulation of specific transcription factors (Nan and Gao, 2019). Extensive studies of DREB in model plants, crops (Toshitsugu et al, 2006), or other economically important plants (Zhao et al, 2014;Xie et al, 2014;Shu et al, 2016) suggest that the number, gene structure, sequences, and functions of this subfamily differ markedly among species.…”
Section: Comparisons Of Dreb Family Composition Between S Spontaneummentioning
confidence: 99%